Sickness certification system in the United Kingdom: qualitative study of views of general practitioners in Scotland. Issue 7431 (22nd December 2003) - Hussey, Susan; Hoddinott, Pat; Wilson, Phil; Dowell, Jon; Barbour, Rosaline
Abstract: Objectives To explore how general practitioners operate the sickness certification system, their views on the system, and suggestions for change. Design Qualitative focus group study consisting of 11 focus groups with 67 participants. Setting General practitioners in practices in Glasgow, Tayside, and Highland regions, Scotland. Sample Purposive sample of general practitioners, with further theoretical sampling of key informant general practitioners to examine emerging themes. Results General practitioners believed that the sickness certification system failed to address complex, chronic, or doubtful cases. They seemed to develop various operational strategies for its implementation. There appeared to be important deliberate misuse of the system by general practitioners, possibly related to conflicts about roles and incongruities in the system. The doctor-patient relationship was perceived to conflict with the current role of general practitioners in sickness certification. When making decisions about certification, the general practitioners considered a wide variety of factors. They experienced contradictory demands from other system stakeholders and felt blamed for failing to make impossible reconciliations. They clearly identified the difficulties of operating the system when there was no continuity of patient care. Many wished either to relinquish their gatekeeper role or to continue only with major changes. Conclusions Policy makers need to recognise and accommodate the range and complexity of factors that influence the behaviour of general practitioners operating as gatekeepers to the sickness certification system, before making changes. Such changes are otherwise unlikely to result in improvement. Models other than the primary care gatekeeper model should be considered.